Kemampuan Guru dalam Mengelola Ekstrakurikuler Tahfidz di MTs Swasta Al-Ittihadiyah Bromo Kecamatan Medan Area Kota Medan - Neliwati Neliwati; May Saroh; Mindi Mentari; Mustika Risti (Journal on Education, 2024)
Success in managing extracurricular tahfidz Al-Qur'an is very dependent on the competence and skills of teachers in terms of understanding, teaching and effective approach methods. There is a problem with the teacher's ability to manage extracurricular tahfidz at Mts Al Ittihadiyah. This can be seen from the phenomena that occur, namely: 1) extracurricular tahfidz which was on hiatus in 2020-2022, 2) lack of students' ability and interest in reading the Al-Qur'an and 3) Limited time that can be allocated for extracurricular activities, accompanied by with the demands of a formal curriculum, it often makes it difficult for teachers to provide intensive attention and assistance in learning tahfidz Al-Qur'an. This research aims to obtain information and a clear picture of teachers' abilities in managing extracurricular Tahfidz at Mts Al Ittihadiyah Bromo, Medan Area District, Medan City. This research uses a qualitative approach with the phenomenological method. Data was collected through observation, interviews and document analysis related to tahfidz extracurricular management. The main respondents were teachers who were involved in these activities. The conclusion of this research is that apart from the teacher's ability to motivate people about the Koran, the environment and parental attention are very important in the success of the tahfidz program at the school.